2006 IEEE/RSJ International Conference on Intelligent Robots and Systems 2006
DOI: 10.1109/iros.2006.282579
|View full text |Cite
|
Sign up to set email alerts
|

Development of Wall-climbing Robots with Sliding Suction Cups

Abstract: This paper investigates the development of wall-climbing robots (WCRs) with sliding suction cups (SSCs) based on the authors' recent research work. The merits and the challenges of the SSCs are analyzed in detail aiming at wheeled WCRs(WWCRs). The dynamic model of WWCRs is presented. It should be noted that the suction force derived from SSCs has great influence on the motion characteristics of WCRs. To utilize the merits, get over the weaknesses of SSCs and increase the service abilities of wall-cleaning robo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…In addition, an airflow model has been developed by utilizing fluid network theory, and its characteristics have been discussed in detail [59]. It has been demonstrated that the developed platform reliably adheres itself to wall surfaces, as well as achieves mobility [60].…”
Section: Vacuum Pump Adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an airflow model has been developed by utilizing fluid network theory, and its characteristics have been discussed in detail [59]. It has been demonstrated that the developed platform reliably adheres itself to wall surfaces, as well as achieves mobility [60].…”
Section: Vacuum Pump Adhesionmentioning
confidence: 99%
“…Qian et al have developed a lifted type wall climbing robot via a rope from the roof without using any actuators on board [60,88]. The robot does not have independent actuation force; instead, it can move up and down by utilizing its own weight and a lifting force from a crane at the rooftop.…”
Section: Rope And/or Rail Grippingmentioning
confidence: 99%
“…A suction unit utilizes air pressure as the pressing force for fixation, and many wall-climbing robots [5,6] use this function to cling onto a wall. In addition, this type of unit can stick to soft material such as body organ.…”
Section: Introductionmentioning
confidence: 99%
“…Wall-climbing robot is a kind of special mobile robot, which can move and work on vertical wall to complete given tasks [1][2][3][4][5]. Although wall-climbing robots have been researched for many years, few practicable wallclimbing robots have been developed to perform very risky works.…”
Section: Introductionmentioning
confidence: 99%